Sustainability in pediatric hospitals: An exploration at the intersection of quality improvement and implementation science - Malone, Sara; Newland, Jason; Kudchadkar, Sapna R.; Prewitt, Kim; McKay, Virginia; Prusaczyk, Beth; Proctor, Enola; Brownson, Ross C.; Luke, Douglas A. (Frontiers in Health Services, 2022)
Although new evidence-based practices are frequently implemented in clinical settings, many are not sustained, limiting the intended impact. Within implementation science, there is a gap in understanding sustainability. Pediatric healthcare settings have a robust history of quality improvement (QI), which includes a focus on continuation of change efforts. QI capacity and sustainability capacity, therefore, serve as a useful concept for connecting the broader fields of QI and implementation science to provide insights on improving care. This study addresses these gaps in understanding of sustainability in pediatric settings and its relationship to QI. This is a cross-sectional observational study conducted within pediatric academic medical centers in the United States. Clinicians surveyed worked with one of three evidence-based clinical programs: perioperative antimicrobial stewardship prescribing, early mobility in the intensive care unit, and massive blood transfusion administration. Participants completed two assessments: (1) the Clinical Sustainability Assessment Tool (CSAT) and (2) a 19-question assessment that included demographics and validation questions, specifically a subset of questions from the Change Process Capability Questionnaire, a QI scale. Initial descriptive and bivariate analyses were conducted prior to building mixed-effects models relating perceived QI to clinical sustainability capacity. A total of 181 individuals from three different programs and 30 sites were included in the final analyses. QI scores were assessed as a single construct (5-point Likert scale), with an average response of 4.16 (higher scores indicate greater QI capacities). The overall CSAT score (7-point Likert scale) was the highest for massive transfusion programs (5.51, SD = 0.91), followed by early mobility (5.25, SD = 0.92) and perioperative antibiotic prescribing (4.91, SD = 1.07). Mixed-effects modeling illustrated that after controlling for person and setting level variables, higher perceptions of QI capabilities were significantly related to overall clinical sustainability. Organizations and programs with higher QI capabilities had a higher sustainability capacity, even when controlling for differences at the individual and intervention levels. Organizational factors that enable evidence-based interventions should be further studied, especially as they relate to sustainability. Issues to be considered by practitioners when planning for sustainability include bedside provider perceptions, intervention achievability, frequency of delivery, and organizational influences.